Exercise induced bronchodilation: a phenomenon more common, greater magnitude and more prolonged in older adults than in adolescents. (4th May 2023) - Welch, Ryan; Lardenoye, Mandy; Kolbe, John; Ellyett, Kevin
Abstract: Objective: There are few studies in clinically healthy subjects describing and quantifying exercise-induced bronchodilation (EIBd ). This study aimed to describe and compare the magnitude and time course changes in post-exercise forced expired volume at the first second (FEV1 ) in healthy adolescents, younger adults, and older adults. Methods: Adolescent ( n  = 73, aged 10–17 years), younger adult ( n  = 35, aged 18–25 years), and older adult ( n  = 25, aged 35–66 years) subjects with normal spirometry z-scores completed a maximal cardiopulmonary exercise test using the standardized exponential exercise test protocol on a cycle ergometer performed at stable temperature and humidity. Spirometry was performed pre-exercise and at 1-, 3-, 5-, and 10-minutes post-exercise to determine the percentage change in FEV1 compared to baseline. EIBd was defined as a  ≥ 5% increase in post-exercise FEV1 . Results: Increases in FEV1 at one-minute post-exercise were observed in the adolescents (1.3%) and young adults (6.0%) with FEV1 returning to baseline after ten minutes. Compared to the adolescents, the older adults showed significantly greater and sustained increases in FEV1 at 1-, 3-, 5-, and 10-minutes post-exercise (6.4, 4.6, 4.7, and 3.8%, p  < 0.05). At 1-minute post exercise a significantly greater proportion of younger adults (54%, p  < 0.01) and older adults (64%, p  < 0.01) demonstrated EIBd compared to the adolescent group (15%). Conclusion: Healthy older adults had a higher prevalence, greater magnitude and more prolonged EIBd compared to healthy adolescent and young adult subjects.